Learning and personal epistemologies among students in three work placement settings. Issue 3 (3rd July 2022) - Hole, Torstein Nielsen; Velle, Gaute; Helleve, Ingrid; Ulvik, Marit; Sætre, Jon Helge; Brøske, Brit Ågot; Raaheim, Arild
ABSTRACT: Recent development in policy and learning theory encourages higher education institutions to send their students out of campus and into work placements. In this paper, we report on students' engagement with various aspects of knowing through practice in work placements. We employed focus group discussions to gather students' accounts of their knowing in the three higher education programmes: Teacher Education, Aqua Medicine, and Music Performance. The students' accounts of knowing were analysed as personal epistemologies. Thereby, we aimed to focus on how enacted practices in work develop students' appraisals of knowing and subjectivities. Three prominent epistemologies were present across all three student groups: professional judgment, professional practice, and professional identity. After the work placements, the students better understand how to enact their knowledge and what knowledge to pursue further. Based on these findings, we hold that there are key educational processes that arise in the interplay between students' situated enactment of practices, knowing, and personal epistemologies through work placements, and propose a conceptual model to frame students' learning in work placements.